2019
DOI: 10.1002/nop2.355
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating an early career transition pathway to community nursing: A Delphi Policy Study

Abstract: AimTo further develop and validate a new model of the early career transition pathway in the speciality of community nursing.DesignDelphi policy approach, guided by a previous systematic review and semi‐structured interviews.MethodsFour rounds of an expert panel (N = 19). Rounds one, two and four were questionnaires consisting of a combination of closed (Likert response) and open‐ended questions. Round three comprised of a focus group conducted using virtual meeting technology.ResultsThe final model demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…The connection with their home community was evident, with nurses/midwives participating in the exchange expressing concerns over leaving their community and losing their connection with it. This finding is supported by recent work undertaken around rapid specialisation of the nursing workforce where a sense of belonging in the community was important [5,9].…”
Section: Embeddednesssupporting
confidence: 59%
See 1 more Smart Citation
“…The connection with their home community was evident, with nurses/midwives participating in the exchange expressing concerns over leaving their community and losing their connection with it. This finding is supported by recent work undertaken around rapid specialisation of the nursing workforce where a sense of belonging in the community was important [5,9].…”
Section: Embeddednesssupporting
confidence: 59%
“…However, some of the regional and remote locations in Australia do not have access to this technology [8], with some not having access to reliable internet services upon which telehealth relies. Nursing in these areas thus forms the mainstay of rural and remote health care, requiring multi-purpose skills to support care from the cradle to the grave, making their repertoire of skills broad but in a sense, also specialised [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ranking within the round determined the stability of panellist responses throughout rounds. 26,27 Domain ranks from rounds 1 and 2 were added together and assigned a final rank. A highranking domain, indicating the importance to panellists, would be represented by having a high mean, low SD and a median of 4 on the 4-point Likert scale.…”
Section: Discussionmentioning
confidence: 99%
“…Well-being [1][2][3][4][5]21,[25][26][27][28][29][30] Social well-being 30 mental well-being 31 emotional well-being 3,23,32 physical well-being 30 cognitive well-being 30 spiritual well-being 30 environmental well-being 30 psychological well-being 23,30 15…”
Section: Total # Of Referencesmentioning
confidence: 99%
“…This notion was highlighted in a study by May et al (2021), which found that the majority of nurses had experienced role conflicts among health care workers due to a lack of understanding regarding their scope of practice. As suggested by Chamberlain et al's (2020) model on career transition to specialist community nursing, one possible mitigating approach is through better 'marketing' to raise awareness regarding the scope of practice in HBC nursing. The greater clarity of nurses' roles in HBC could potentially improve the recruitment into HBC nursing.…”
Section: The Transitioning Experiencementioning
confidence: 99%